2016
DOI: 10.1590/0034-737x201663020009
|View full text |Cite
|
Sign up to set email alerts
|

Capacidade de combinação de genitores de cenoura para caracteres de produtividade de raízes e tolerância à queima-das-folhas

Abstract: RESUMO A demanda de mercado por uniformidade e produtividade de raízes comerciais de cenoura tem priorizado materiais híbridos em detrimento às variedades de polinização aberta. Neste sentido, objetivou-se com este trabalho estimar as capacidades de combinação de genitores de cenoura para os caracteres produtividade de raiz e resistência à queima-das-folhas. Os experimentos foram realizados no Gama, DF, nos anos agrícolas de 2012/13 e 2013/14. Foram avaliados 33 híbridos de cenoura, originados de cruzamentos e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(16 reference statements)
1
2
0
1
Order By: Relevance
“…The high and negative correlation (-0.77) between MRM and tolerance to leaf blight was demonstrated by Brito et al (1997). These results agree with those presented by Pereira et al (2012) and Carvalho et al (2016), who found a negative correlation between the MRM (-0.52 and -0.31) and TRM (-0.59 and -0.47) of populations 561 and 586 with the leaf blight severity. The fact that the MRM is correlated with ADPC makes sense, since plants were more tolerant to leaf blight and kept their leaves for longer, thereby enabling conditions for the development of the roots until they reach a marketable standard.…”
Section: Resultssupporting
confidence: 93%
“…The high and negative correlation (-0.77) between MRM and tolerance to leaf blight was demonstrated by Brito et al (1997). These results agree with those presented by Pereira et al (2012) and Carvalho et al (2016), who found a negative correlation between the MRM (-0.52 and -0.31) and TRM (-0.59 and -0.47) of populations 561 and 586 with the leaf blight severity. The fact that the MRM is correlated with ADPC makes sense, since plants were more tolerant to leaf blight and kept their leaves for longer, thereby enabling conditions for the development of the roots until they reach a marketable standard.…”
Section: Resultssupporting
confidence: 93%
“…Currently, carrot breeding programs aim to develop mainly hybrid cultivars. Although market has focused on this type of cultivar; multi-character selection in breeding base populations is an important phase in breeding programs (Carvalho et al, 2016).…”
Section: Scientific Communicationmentioning
confidence: 99%
“…The carrot breeding collection of the Embrapa genetic breeding program includes variability that can be exploited when releaseding new free-pollinated cultivars or lines for obtaining hybrids. Carrot breeding programs generally prioritise characteristics such as yield and root quality, in addition to resistance to disease (CARVALHO et al, 2016). However, simultaneous selection for these characteristics, with a view to adequate and balanced gains, is a challenge for breeding programs, since most are of quantitative inheritance and may even be correlated, implying the possibility of selection for a certain characteristic changing expression of the others.…”
Section: Introductionmentioning
confidence: 99%
“…A coleção de trabalho de cenoura do programa de melhoramento genético da Embrapa dispõe de uma variabilidade que pode ser explorada visando o lançamento de novas cultivares de polinização livre ou de linhagens para a obtenção de híbridos. Normalmente, em programas de melhoramento genético de cenoura as características priorizadas são: rendimento e qualidade de raiz, além da resistência a doenças (CARVALHO et al, 2016). Contudo, a seleção simultânea para essas características, visando ganhos adequados e equilibrados, é um desafio para os programas de melhoramento genético, em razão da maioria serem de herança quantitativa, podendo ainda estar correlacionadas, o que implica na possibilidade da seleção em determinada característica, alterar a expressão em outras.…”
Section: Introductionunclassified